A generalized bird pollination system in Schotia brachypetala (Fabaceae). (25th May 2022) - Kiepiel, I.; Brown, M.; Johnson, S. D.
ABSTRACT: Bird pollination systems are diverse, ranging from narrow‐tubed flowers pollinated by specialist nectarivores such as hummingbirds and sunbirds, to relatively open flowers pollinated by opportunistic ( i.e . generalist) nectarivores. The role of opportunistic avian nectarivores as pollinators has historically been under‐appreciated. A key aspect to understanding the importance of opportunistic birds as pollinators is to investigate how efficiently they transfer pollen among flowers. Here, we document the pollination and breeding systems of Schotia brachypetala, a southern African tree known as the 'weeping boer‐bean' on account of its prolific production of dilute hexose‐dominated nectar. The cup‐shaped flowers of this tree attract a large number of bird species, including both opportunistic and specialist nectarivores. We identified floral visitors using observations and camera traps and quantified the floral traits responsible for animal attraction. We documented the breeding system, used selective pollinator exclusion to test the contribution of birds to fecundity, and performed supplemental pollination to test for pollen limitation. Single‐visit pollen deposition trials were undertaken to determine the efficacy of bird pollinators. Controlled hand‐pollination experiments showed that S . brachypetala is genetically self‐incompatible and therefore dependent on pollinators for seed production. Supplemental hand‐pollination experiments showed that natural fecundity is limited by either the amount and/or the quality of pollen on stigmas. Flowers from which birds but not insects were experimentally excluded set fewer seeds than open control flowers. Opportunistic birds deposited more pollen per visit than did specialist sunbirds. We conclude that S . brachypetala has a generalized bird pollination system that mainly involves opportunistic nectarivores. Abstract : The relatively open, cup‐shaped flowers of Schotia brachypetala are pollinated by both specialist and opportunistic nectarivorous birds; however, opportunistic birds are likely to contribute more to fecundity due to their greater abundance and per‐visit pollen deposition on stigmas.